Analyses and forecasting evaluation of GDP of India using ARIMA model - Ramandeep Singh Arneja, Navdeep Kaur; A.K. Saihjpal (International Journal of Advanced Science and Technology, 2020)
This paper has attempted to forecast the Gross Domestic Product (GDP) with applying the Box Jenkins forecasting method. We have taken the historical data of GDP and to anticipate India’s Gross Domestic Product while utilizing period arrangement information for the period from 1980 till 2017. The data has been collected for the Thirty-seven years and effort has been made to construct a forecast model for GDP using Autoregressive Integrated Moving Average Model (ARIMA) to construct the hypothetical model which is ARIMA for evaluating the India’s GDP. Out of an assortment of determining models ARIMA (1, 1, 7) model has been applied to figure the GDP for thirty-seven years running from 1980 to 2017. The outcome proliferated that the wellness of AR (1) I (1) MA (7) parameters for making future forecasts. It is deciphered that the GDP of India would be rising ceaselessly over the assessed period. The model has been validated through diagnostic checking using the correlogram of the residual.